Online preconcentration by electrokinetic supercharging for separation of endocrine disrupting chemical and phenolic pollutants in water samples - Abdul Karim, N. I. (Wiley-VCH Verlag, 2016)
Online preconcentration using electrokinetic supercharging (EKS) was proposed to enhance the sensitivity of separation for endocrine disrupting chemical (methylparaben (MP)) and phenolic pollutants (2-nitrophenol (NP) and 4-chlorophenol (CP)) in water sample. Important EKS and separation conditions such as the concentration of BGE; the choice of terminating electrolyte (TE); and the injection time of leading electrolyte (LE), sample, and TE were optimized. The optimum EKS-CE conditions were as follows: BGE comprising of 12 mM sodium tetraborate pH 10.1, 100 mM sodium chloride as LE hydrodynamically injected at 50 mbar for 30 s, electrokinetic injection (EKI) of sample at –3 kV for 200 s, and 100 mM CHES as TE hydrodynamically injected at 50 mbar for 40 s. The separation was conducted at negative polarity mode and UV detection at 214 nm. Under these conditions, the sensitivity of analytes was enhanced from 100- to 737-fold as compared to normal CZE with hydrodynamic injection, giving LOD of 4.89, 5.29, and 53 µg/L for MP, NP and CP, respectively. The LODs were adequate for the analysis of NP and CP in environmental water sample having concentration at or lower than their maximum admissible concentration limit (240 and 2000 µg/L for NP and CP). The LOD of MP can be suitable for the analysis of MP exists at mid-microgram per liter level, even though the LOD was slightly higher than the concentration usually found in water samples (from ng/L to 1 µg/L). The method repeatabilities (%RSD) were in the range of 1.07–2.39% (migration time) and 8.28–14.0% (peak area).